Neonatal cholestasis can be the first symptom of McCune–Albright syndrome: A case report - Satomura, Yoshinori (World J Clin Pediatr, 2021)
BACKGROUND: McCune–Albright syndrome (MAS) is caused by postzygotic somatic mutations of the GNAS gene. It is characterized by the clinical triad of fibrous dysplasia, café-au-lait skin spots, and endocrinological dysfunction. Myriad complications in MAS, including hepatobiliary manifestations, are also reported. CASE SUMMARY: This is a case of a 4-year-old boy who presented with MAS with neonatal cholestasis. He was suspected to have Alagille syndrome due to neonatal cholestasis with intrahepatic bile duct paucity in liver biopsy, peripheral pulmonary artery stenosis, and renal tubular dysfunction. By the age of 2 years, his cholestatic liver injury gradually improved, but he had repeated left femoral fractures. He did not exhibit endocrinological abnormality or café-au-lait skin spots. However, MAS was suspected due to fibrous dysplasia at the age of 4 years. No mutation was identified in the GNAS gene in the DNA isolated from the peripheral blood, but an activating point mutation (c.601C>T, p.Arg201Cys) was observed in the DNA extracted from the affected bone tissue and that extracted from the formalin-fixed paraffin-embedded liver tissue, which was obtained at the age of 1 mo. CONCLUSION: MAS should be considered as a differential diagnosis for transient cholestasis in infancy.